VOLUME TEGAKAN Acacia mangium PADA UJI PEROLEHAN GENETIK DENGAN KERAPATAN TEGAKAN TINGGI - Dwi Kartikaningtyas; Teguh Setyaji; Arif Nirsatmanto (Jurnal Pemuliaan Tanaman Hutan, 2017)
High initial stand density is commonly practiced in forest plantations subjected to produce high quality logs through successive thinnings. In this study, genetically improved seed of Acacia mangium was verified in genetic gain trial using high initial stand density. The trial was established in Jonggol, West Java and laid out in randomized complete block design with high initial stand density of 2500 trees/ha or in spacing of 2 x 2 m. The improved seeds tested in the trial were collected from four seedling seed orchards (SSOs). As a control, unimproved seeds from seed production area (SPA) were also planted together in the trial. The assessment of stand volume productivity was periodically conducted at two, three and four years of age. The results of study showed that the improved seeds from the four SSOs out performed the unimproved one. However, the significant difference among the seed sources was initially found at the four years of age. The average stand volumes of improved seed were 58.56m3/ha, 94.87m3/ha and 163.8m3/ha for two, three, and four years of age, respectively. The superiority of improved seed over the unimproved one ranged from 23%-36% (two years), 6%-30% (three years) and 2%-22% (four years). The four SSOs showed different behaviours in response to high stand density. Improved seed from SSOs with higher selection intensity was likely to be more tolerant to high stand density.